Mechanisms and Therapy for Cancer Metastasis to the Brain - Franchino, Federica; Rudà, Roberta; Soffietti, Riccardo (Frontiers in Oncology, 2018)
Advances in chemotherapy and targeted therapies have improved survival in cancer patients with an increase of the incidence of newly diagnosed brain metastases (BM). Intracranial metastases are symptomatic in 60-70% of patients. MRI with gadolinium is more sensitive than CT and advanced neuroimaging techniques have been increasingly used in the detection, treatment planning, and follow-up of BM. Apart from the morphological analysis, the most effective tool for characterizing BM is immunohistochemistry. Molecular alterations not always reflect those of the primary tumor. More sophisticated methods of tumor analysis detecting circulating biomarkers in fluids (liquid biopsy), including circulating DNA, circulating tumor cells (CTCs), and extracellular vesicles (EVs), containing tumor-DNA and macromolecules (miRNA), have shown promise regarding tumor treatment response and progression. The choice of therapeutic approaches is guided by prognostic scores (Recursive Partitioning Analysis-RPA and diagnostic specific Graded Prognostic Assessment-DS-GPA). The survival benefit of surgical resection seems limited to the subgroup of patients with controlled systemic disease and good performance status. Leptomeningeal dissemination (LMD) can be a complication, especially in posterior fossa metastases undergoing a “piecemeal” resection. Radiosurgery of the resection cavity may offer comparable survival and local control as postoperative WBRT. WBRT alone is now the treatment of choice only for patients with single or multiple brain metastases not amenable to surgery or radiosurgery, or with poor prognostic factors. To reduce the neurocognitive sequelae of WBRT intensity modulated radiotherapy (IMRT) with hippocampal sparing, and pharmacological approaches (memantine and donepezil) have been investigated. In the last decade a multitude of molecular abnormalities have been discovered. Approximately 33% of patients with NSCLC tumors and EGFR mutations develop BM, that are targetable with different generations of TKI (tyrosine kinase inhibitors: gefitinib, erlotinib, afatinib, icotinib, osimertinib). Other “druggable” alterations seen in up to 5% of NSCLC patients, are the rearrangements of the “anaplastic lymphoma kinase” (ALK) gene TKI (crizotinib, ceritinib, alectinib, brigatinib and lorlatinib). In HER2-positive breast cancer targeted therapies have been widely used (trastuzumab, trastuzumab-emtansine, lapatinib-capecitabine and neratinib). Novel targeted and immunotherapeutic agents have also revolutionized the systemic management of melanoma (ipilimumab, nivolumab, pembrolizumab and BRAF-inhibitors dabrafenib and vemurafenib).